Evaluasi Efektivitas Sistem Manual Peminjaman Buku Perpustakaan di Sekolah ABC Menggunakan Metode PIECES - Rani Kause; Rizal Rizal; Veronikanatalia Veronikanatalia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the effectiveness of the manual book lending system still applied in the library of ABC School. The evaluation uses the PIECES method, which covers six key aspects: Performance, Information, Economy, Control, Efficiency, and Service. The research applies a descriptive quantitative approach, utilizing data collection techniques including Likert-scale questionnaires, structured interviews, and direct observation. The sample consists of 34 active respondents, including 26 students, 6 teachers, and 2 librarians. The results show that all PIECES indicators received very low average scores: Performance (1.59%), Information (2.23%), Economy (1.64%), Control (1.65%), Efficiency (1.67%), and Service (1.69%). These results indicate that the manual system in place is highly ineffective in supporting the library’s lending Services. The current system is not only slow and prone to errors, but also inefficient in terms of time and resource utilization. Based on these findings, it is recommended that ABC School modernize its library system by implementing a digital or computerized Information system to improve Service Efficiency, data accuracy, and user satisfaction.